2021
DOI: 10.1038/s41598-021-86651-y
|View full text |Cite
|
Sign up to set email alerts
|

Transverse aortic constriction induces gut barrier alterations, microbiota remodeling and systemic inflammation

Abstract: Accumulating evidence suggests that modifications of gut function and microbiota composition might play a pivotal role in the pathophysiology of several cardiovascular diseases, including heart failure (HF). In this study we systematically analysed gut microbiota composition, intestinal barrier integrity, intestinal and serum cytokines and serum endotoxin levels in C57BL/6 mice undergoing pressure overload by transverse aortic constriction (TAC) for 1 and 4 weeks. Compared to sham-operated animals, TAC induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Male SD rats (220–250 g), purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. [Animal license number: SCXK (Beijing) 2017–0302], were fed adaptively for 3 days. A model of HF was established surgically through transverse aortic constriction (TAC) operation as has been described ( Ruppert et al, 2020 ), which is one of the most widespread preclinical models of cardiac hypertrophy and HF induced by pressure overload ( Boccella et al, 2021 ). Following anesthesia with sodium pentobarbital (40 mg/kg) and subsequently a left anterolateral thoracotomy, the aortic arch between the brachiocephalic trunk and the left common carotid artery was exposed and then constricted to the size of a 21-gauge needle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male SD rats (220–250 g), purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. [Animal license number: SCXK (Beijing) 2017–0302], were fed adaptively for 3 days. A model of HF was established surgically through transverse aortic constriction (TAC) operation as has been described ( Ruppert et al, 2020 ), which is one of the most widespread preclinical models of cardiac hypertrophy and HF induced by pressure overload ( Boccella et al, 2021 ). Following anesthesia with sodium pentobarbital (40 mg/kg) and subsequently a left anterolateral thoracotomy, the aortic arch between the brachiocephalic trunk and the left common carotid artery was exposed and then constricted to the size of a 21-gauge needle.…”
Section: Methodsmentioning
confidence: 99%
“…New therapeutic strategies are needed to be introduced clinically for protecting against pressure overload-induced cardiac injury ( Li X. et al, 2021 ) or targeting adverse post-MI left ventricle remodeling ( Germano et al, 2020 ). Researchers highlight the potential of intestinal microbiota and NLRP3 inflammasomes to impact ventricular remodeling, which hold promise as effective targets for improving cardiac functions in HF ( Boccella et al, 2021 ; Zhao et al, 2021 ). The beneficial effects of QL on cardiac hypertrophy, ventricular remodeling, and HF through multiple pathways have been widely reported ( Gao et al, 2018 ; Lu et al, 2020 ; Wang et al, 2017 ).…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota and their metabolites produced from dietary metabolism have been linked to HF. To this extent, gut dysbiosis with decreased microbial richness and increased gut permeability has been reported in patients with HF (57,58), as well as in mice with pressure overload-induced HF (59).…”
Section: Heart Failurementioning
confidence: 99%
“…Gut microbiota and their metabolites produced from dietary metabolism have been linked to HF. To this extent, gut dysbiosis with decreased microbial richness and increased gut permeability has been reported in patients with HF ( 57 , 58 ), as well as in mice with pressure overload-induced HF ( 59 ). Further studies in humans have shown that the gut microbiome-derived metabolite TMAO is increased in HF and that its levels are associated with poor prognosis ( 60 64 ).…”
Section: Overview Of the Interplay Between The Gut Microbiome And The...mentioning
confidence: 99%